ВЫБОР МЕТОДА ЛЕЧЕНИЯ ПАЦИЕНТОВ С МОЧЕКАМЕННОЙ БОЛЕЗНЬЮ АНОМАЛИЙНЫХ ПОЧЕК («Наука и здравоохранение», 2026)
This observation is an example of surgical treatment of patients with renal anomalies (left-side incomplete double ureter,ureteropelvic segment stenosis) with urolithiasis. We performed lumbotomy, pelviolithotomy with ureteropelvic segment stenosis correction. Thus, in the presence of comorbidity with urolithiasis, remains an important question about the open surgical treatment for the causes of lithogenesis.